School Value-Added and Long-Term Student Outcomes - Lars J. Kirkebøen (Center for Economic Studies and ifo Institute (CESifo), 2022)
Several recent studies find that interventions in schools can have important lasting consequences for students, and that schools differ in their contribution to students' learning. However, there is less research investigating how these differences between schools influence longer-term outcomes, especially outside the US. In this paper I study the value-added (VA) of Norwegian schools, where between-school differences are smaller than in the US. I find that VA indicators are able to predict in-school performance without bias. Furthermore, VA is strongly related to long-term outcomes, and differences between schools in VA correspond to meaningful differences in long-term outcomes. For example, a one standard deviation higher VA corresponds to 1.9 percent higher earnings at around age 32. Three quasi-experiments using variation from student mobility and changes in neighborhoods' assignment to schools indicate that the differences captured by the VA indicators do indeed reflect differences in school quality, rather than unobserved student characteristics. Analyses of teacher grades and exam scores suggest that the former are heavily influenced by relative grading, and that the effect of exam score VA on long-term outcomes reflects the effects of competencies and skills acquired in school. In addition to shedding light on the differences in and mechanisms of school quality, the findings help connect learning outcomes with later labor market outcomes, e.g. for cost-benefit analysis of interventions in schools.
Keywords: Q54; D70; D50; 330; climate economics; international environmental agreements; coalition formation; heterogeneous countries; integrated assessment models